The Spirit of Pancasila in Revolution of Accounting Education - Rini, Nurul Kompyu; Wulandari, Anis (Accounting Department,, 2022)
Purpose — Almost all corruption problems occur; one of the actors is an accountant. Why do many accountants get caught up in these cases, especially in Indonesia? So far, the accounting profession in Indonesia has continued to improve to align itself with the world accounting profession. Design/methodology/approach—This research study examines the pillars of nationality in Pancasila as the foundation for analyzing the cause of financial fraud. Findings—Accounting affects all parties, whether directly involved or not. For those directly involved, it is possible to secure their welfare. In contrast, those who are not directly involved will feel their contribution in the form of facilities regulated by the internal (company) and external (government) provisions. Practical implications—As one of the pillars of nationality in Pancasila, nationality is expected to be used as a foundation for the accounting profession, enabling professional accountants to carry out life and obligations while developing science while still having an Indonesian heart and soul. Originality/value — Through the five pillars of nationality in Pancasila, which are included in the accounting education process as a balance between secularity material and Pancasila and ethics originating from Indonesian national identity. Keywords — Pancasila, accounting education, accountant, financial fraud Paper type — Research Paper